Novel Tangisan Batang Pudu: Kajian Ekokritik Kerusakan Lingkungan dan Kepedulian Terhadap Alam - Fauziah Nurul Islamiah; Juanda Juanda; Suarni Syam Saguni (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
The environment is the focus of attention because of the large amount of damage caused by human behavior and the impact on nature. Therefore, this research aims to examine the forms of environmental damage and the characters' attitudes of love and concern for nature in the novel Tangisan Batang Pudu. The method used in this research is a descriptive qualitative research method. The data and data sources for this research are text quotations contained in the novel Tangisan Batang Pudu by Musa Ismail. This novel was published by Deepublish Publisher, Yogyakarta in 2020, first printing, 156 pages thick. The data analysis technique for this research was carried out by identification, classification, analysis and description of data. The results of the research show that there are six aspects of Greg Garrard's environmental damage, namely, pollution, wilderness, disasters, housing/residence, animals, and the earth. Then there is also a form of environmental ethics, namely a form of human affection and concern for the natural environment. Based on the results of data analysis, the more dominant data is in the form of environmental damage. This is proven in the novel which was written against the background of environmental pollution by companies in the Batang Pudu river which resulted in poor people in the surrounding area suffering from the environmental damage that occurred. The contribution of this research will be a means of developing literature and can be used as a reference in the development of relevant research in the future, and can increase insight and understanding regarding the study of ecocritical theory which will make readers aware to care more about the surrounding natural environment. Future research for this novel is expected to study and research the novel Tangisan Batang Pudu by Musa Ismail with different theories and study methods as a form of scientific development in the field of Indonesian language and literature.